The Hippo signaling pathway contributes to the 2,5-Hexadion-induced apoptosis of ovarian granulosa cells - Yi Sun; Huiting Chen; Sichuan Chen; Xueming Xu; Wenchang Zhang; Yuchen Li (BMC, 2023)
Abstract Although n-hexane can induce ovarian damage by inducing ovarian granulosa cell (GC) apoptosis, the mechanism underlying this induction of apoptosis has not been fully elucidated. In this study, rat ovarian GCs were exposed to different concentrations of 2,5-hexanedione (2,5-HD) (the main metabolite of n-hexane) in vitro to observe apoptosis, and the mechanism was further explored via mRNA microarray analysis. Hoechst 33258 staining and flow cytometry suggested that the apoptosis rate of ovarian GC apoptosis was significantly increased in the 2,5-HD-treated group. Subsequently, microarray analysis revealed that a total of 5677 mRNAs were differentially expressed, and further GO and KEGG analyses revealed that the differentially expressed genes were significantly enriched in many signaling pathways, including the Hippo pathway. A total of 7 differentially expressed genes that function upstream of the Hippo signaling pathway (Nf2, Wwc1, Ajuba, Llgl1, Dlg3, Rassf6 and Rassf1) were selected to confirm the microarray results by qRT-PCR, and the expression of these genes did change. Subsequently, the expression of key effector genes (Yap1, Mst1 and Lats1) and target genes (Ctgf and Puma) of the Hippo signaling was measured, and the results suggested that the mRNA and protein levels of Yap1, Mst1, Lats1, and Ctgf were significantly decreased while those of Puma were significantly increased after 2,5-HD treatment. Further CO-IP analysis suggested that the interaction between YAP1 and TEAD was significantly reduced after 2,5-HD treatment, while the interaction between YAP1 and P73 was not affected. In summary, during the 2,5-HD-induced apoptosis of ovarian GCs, the Hippo signaling pathway is inhibited, and downregulation of the pro-proliferation gene Ctgf and upregulated of the pro-apoptosis gene Puma are important. Decreased Ctgf expression was associated with decreased binding of YAP1 to TEAD. However, increased PUMA expression was not associated with YAP1 binding to P73.